Nano-Cerium: A Promising Additive for Enhancing Cryosurvival and Antioxidant Defence in Buffalo Bull Semen - Chaudhari, Meet T; Parmar, Kiran H; Patel, Richakumari M; Pathan, Mohsin M; Chaudhari, Dinesh V; Parmar, Jignesh J; Hadiya, Kamlesh K (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
The present study was aimed to evaluate the effect of cerium oxide nanoparticles (CeO2NPs) supplementation in Tris-fructose-yolk glycerol (TFYG) extender on post-thaw semen quality of buffalo bulls. Semen ejaculates (n=18) collected from four healthy, sexually  mature bulls using an artificial vagina were pooled and divided into four treatment groups containing 0 (control), 25, 50, and 75 μg/ mL CeO2NPs in TFYG extender. The samples were processed, equilibrated, cryopreserved, and evaluated post-thaw for sperm motility,  viability, morphology, plasma membrane integrity, acrosome integrity, malondialdehyde (MDA), and total antioxidant capacity (TAC).  Post-thaw sperm motility was significantly higher (p
Keywords: Antioxidant status, Buffalo bulls, Cerium oxide nanoparticles, Cryopreservation, TFYG extender